Stress and Burnout in Teachers During Times of Pandemic - Vargas Rubilar, Natalia; Oros, Laura Beatriz (Frontiers in Psychology, 2021)
In Argentina, once mandatory isolation was declared due to the COVID-19 pandemic, teachers of all educational levels and modalities had to substantially modify their way of working. The aim of this study was to identify the work situations that education professionals perceived as threats under the modality of non-face-to-face teaching, and to describe the level of perceived stress and its possible effect on psychophysical symptoms. Likewise, it sought to examine possible differences in the manifestations of burnout depending on the level of perceived stress and associated symptoms. An empirical study with a cross-sectional design was developed, in which 9,058 Argentine teachers, who had to complete self-report measures, participated. The sampling method was non-random, using an online procedure of reclusion of volunteers. Descriptive techniques and nonparametric tests were used for data analysis. More than 60 % of the educators reported high and moderately high levels of stress. The predominant stressors were uncertainty about the consequences of the pandemic, work overload and inadequate working environment. The more stress they perceived, the higher the manifestation of unwanted psychophysical symptoms. Professional burnout was higher for teachers with a higher load of stress and with more psychophysical indicators of discomfort. These results reveal the psychological impact of the COVID-19 pandemic on the education staff, and encourage the development of intervention measures to preserve the health of professionals.